2013
DOI: 10.1111/and.12160
|View full text |Cite
|
Sign up to set email alerts
|

Effect of kolaviron, a biflavonoid complex fromGarcinia kolaseeds, on the antioxidant, hormonal and spermatogenic indices of diabetic male rats

Abstract: The antihyperglycaemic effect of kolaviron (KV), a biflavonoid from Garcinia kola has been established in previous studies. In this study, we investigated the effect of KV (200 mg kg(-1) ) on the antioxidant, hormonal and spermatogenic indices of alloxan-diabetic male rats, and metformin hydrochloride (MET) (30 mg kg(-1) ) served as standard drug. The results showed that KV and MET significantly (P < 0.05) decreased the fasting blood glucose of the diabetic rats. Also, untreated and MET-treated diabetic groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 44 publications
3
14
0
1
Order By: Relevance
“…The study conducted by Adaramoye and Lawal (2014) on diabetic male rats showed that metformin is able to restore follicle-stimulating hormone, leutinizing hormone, and testosterone (Adaramoye, Lawal, 2014). Likewise, oral administration of metformin succeeded to restore testosterone level back to normal in diabetic rats (Ayuob, Murad, Ali, 2015).…”
Section: Positive Effectsmentioning
confidence: 98%
See 2 more Smart Citations
“…The study conducted by Adaramoye and Lawal (2014) on diabetic male rats showed that metformin is able to restore follicle-stimulating hormone, leutinizing hormone, and testosterone (Adaramoye, Lawal, 2014). Likewise, oral administration of metformin succeeded to restore testosterone level back to normal in diabetic rats (Ayuob, Murad, Ali, 2015).…”
Section: Positive Effectsmentioning
confidence: 98%
“…Later in vivo system study on diabetic rats clearly showed that oral treatment with metformin (50 mg/kg/day, for 4 weeks) in combination with pioglitazone, another antidiabetic drug, at 1 mg/kg increases the caudal sperm count and decreases sperm morphology defects 592 (Rabbani, Devi, Khanam, 2010). Moreover, epididymal sperm count, motility, and morphology were improved in diabetic rats upon treatment with metformin at 30 mg/kg/ day for 6 weeks (Adaramoye, Lawal, 2014). Furthermore, diet-induced obesity rats fed orally with metformin for 12 weeks had higher epididymal sperm count and motility (Fang et al, 2012).…”
Section: Positive Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spermatozoa are particularly susceptible to lipid peroxidation (peroxidative damage) due to high concentration of PUFAs, which are related to arranging of spermatogenesis, sperm maturation, acrosome reaction, capacitation and poor antioxidant capacity and membrane fusion. The process of LPO in spermatozoon might demolish the lipid structure of spermatozoa membranes, also it may cause to fast loss of the intracellular ATP, decrease sperm viability, increase medium grade morphological defects and inhibit spermatogenesis in extreme situations (Adaramoye & Lawal, ; Farombi & Nwaokeafor, ; Vernet, Aitken, & Drevet, ). The excessive Cu in diet of rats might cause the membrane damage and LPO.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of Cu in seminal plasma and serum of fertile male rats were significantly lower than those in subfertile male rats (Aydemir et al, 2006;Eidi et al, 2010). (Adaramoye & Lawal, 2014;Farombi & Nwaokeafor, 2005;Vernet, Aitken, & Drevet, 2004). The excessive Cu in diet of rats might cause the membrane damage and LPO.…”
Section: Discussionmentioning
confidence: 99%